Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1149/1945-7111/ac2467
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Long-Chain Polysulfide Formation in Li-S Batteries by Using Localized Low Concentration Highly Fluorinated Electrolytes

Abstract: Electrolytes that suppress the formation of long-chain polysulfides and limit the sulfur (S) cathode dissolution and polysulfide shuttle effect, while maintaining high active material utilization and long cycle life, have long been sought for advancing Li-S battery applications. Here we demonstrate that localized electrolytes based on fluorinated ethers with the total salt concentration of only 0.1 M show remarkable performance characteristics. By systematically reducing the fraction of sulfolane (SL) as a cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Due to the sluggish Li + transport, the specific capacity delivered in the neat ILE is low, and the discharge profile does not show any flat voltage plateau. When the LCILEs are employed, the discharge profiles exhibiting a slope around 2.1 V and a plateau slightly below 2.0 V are different from those observed with 1 M LiTFSI in DME/DOL, but similar to those reported from locally concentrated electrolytes based on organic solvents [85, 88] . Rebecca et al.…”
Section: Electrochemical Propertiesmentioning
confidence: 72%
See 2 more Smart Citations
“…Due to the sluggish Li + transport, the specific capacity delivered in the neat ILE is low, and the discharge profile does not show any flat voltage plateau. When the LCILEs are employed, the discharge profiles exhibiting a slope around 2.1 V and a plateau slightly below 2.0 V are different from those observed with 1 M LiTFSI in DME/DOL, but similar to those reported from locally concentrated electrolytes based on organic solvents [85, 88] . Rebecca et al.…”
Section: Electrochemical Propertiesmentioning
confidence: 72%
“…When the LCILEs are employed, the discharge profiles exhibiting a slope around 2.1 V and a plateau slightly below 2.0 V are different from those observed with 1 M LiTFSI in DME/DOL, but similar to those reported from locally concentrated electrolytes based on organic solvents. [85,88] Rebecca et al recently reported that the difference between the discharge profiles obtained with a conventional ether electrolyte and locally concentrated sulfolane electrolytes originates from a minimised long-chain polysulphides formation with the addition of hydrofluoroether co-solvents in the locally concentrated electrolytes. The poor solubility of Li + in the HFE leads to a shift to favouring short chain length polysulphides in the discharge of sulphur.…”
Section: Li-s Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Glaser et al used 1,1,2,2‐tetrafluoroethyl 2,2,3,3‐tetrafluoropropylether (HFE) as a cosolvent to sulfolane (SL) to make a localized low concentration electrolyte (LLCE) with 0.1 m LiTFSI. [ 37 ] They observed that increasing the HFE changed the redox reaction on the cathode side. In short, the S was being lithiated to Li 2 S in a solid‐state reaction, significantly decreasing polysulfide dissolution.…”
Section: Electrolyte Optimizationmentioning
confidence: 99%
“…The volume expansion of sulfur toward Li 2 S 2 /Li 2 S gives rise to the structural damage of the cathode. , The shuttling effect of polysulfides during charging and discharging leads to capacity loss and further lifespan decrease . Researchers have tried to solve these problems through sulfur host regulation, electrolyte engineering, separator modification, and self-standing interlayer insertion. Among these, the self-standing interlayer introduction stands out to be simple and effective because it provides not only considerable physical entrapment for polysulfides but also further chemical adsorption and conversion after further modification. Therefore, the material selection of the interlayer is of great importance.…”
Section: Introductionmentioning
confidence: 99%